2011
DOI: 10.1007/s00330-011-2198-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative in vivo MRI evaluation of lumbar facet joints and intervertebral discs using axial T2 mapping

Abstract: This study demonstrates the feasibility of a combined T2 mapping approach for the facet joints and intervertebral discs using a single axial slab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 31 publications
2
34
2
Order By: Relevance
“…We performed axial T2, T2* and T1ρ mapping of the LFJ and the IVD (Table 3); the values of the LFJ are close to those for knee joint cartilage[7, 22]. The mean and range of T1ρ values for the FJ cartilage in our study are the first such measurements to be reported.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…We performed axial T2, T2* and T1ρ mapping of the LFJ and the IVD (Table 3); the values of the LFJ are close to those for knee joint cartilage[7, 22]. The mean and range of T1ρ values for the FJ cartilage in our study are the first such measurements to be reported.…”
Section: Discussionmentioning
confidence: 52%
“…Particularly in the early stages of IVD degeneration, it can be difficult to detect the small morphological changes of the LFJ on plain radiography, computed tomography, or conventional magnetic resonance imaging (MRI)[4]. In addition, morphological MRI grading systems for LFJ dysfunction (e.g., Weishaupt grading) tend to have poor inter-rater agreement[7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, GAG depletion has been demonstrated to play a central part in these degenerative processes which may lead to morphological degradation of IVDs, vertebral bodies, endplates and FJs 11,23,24 . With gagCEST imaging, it is possible to non-invasively visualize and analyze GAG content of the IVDs 15,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical changes have been suspected to be a precursor to early IVD degeneration 11,23,24 . In particular, GAG depletion has been demonstrated to play a central part in these degenerative processes which may lead to morphological degradation of IVDs, vertebral bodies, endplates and FJs 11,23,24 .…”
Section: Discussionmentioning
confidence: 99%